Optical Behavior Analysis of Negative Wavelength Detuning in SMFP-LD and Its Effect on Multi-RF Generation - Hao Chen; Bikash Nakarmi; M. Rakib Uddin; Shilong Pan (IEEE Photonics Journal)
Injection locking with positive wavelength detuning has been used for a long time for optical signal processing, signal generation, and computing. Recently a new technique, “injection locking with negative wavelength detuning,” has been introduced and has shown its potential on microwave generation. In this paper, we analyze optical behavior of negative injection locking and its impact on multi-RF generation using single-mode Fabry-Pérot laser diode (SMFP-LD). SMFP-LD is composed of a commercial multi-mode FP-LD with a built-in external cavity. As compared to conventionally used positive detuning optical injection, the negative detuning optical injection (NOI) shows advantageous differences on the suppression of the dominant mode, side modes, bistability property, and the hysteresis width. The laws of free carrier motion in the laser cavity is leveraged to explain these phenomena. Based on the analysis, the NOI in the SMFP-LD has a distinct advantage for multi-RF generation and switching RF signals. In addition, the output performances of the generated RF signal such as linewidth, power-dependent frequency shifting, and signal-to-noise ratio (SNR) are investigated.